Incidencia de Mycobacterium bovis en bovinos faenados en el matadero municipal del cantón Ventanas Provincia de Los Ríos. - López Aguirre, Jeniffer Karina (2025)
Bovine tuberculosis is an infectious disease caused by the GRAN-positive bacterium Mycobacterium bovis, which affects cattle and other domestic and wild animals, being a zoonotic disease that is also present in humans. The present research work, whose main objective was to determine the incidence of Mycobacterium bovis in cattle slaughtered in the municipal slaughterhouse of Cantón Ventanas province of Los Ríos, evaluated bovine tuberculosis and its incidence through the correlation of variables; according to age, sex, racial group and origin; in addition, a macroscopic post mortem analysis of organs, lymph nodes and viscera was carried out. This research work used a descriptive method of macroscopic experimental observation. This method was based on the percentage method to determine the percentage of incidence of Mycobacteriun bovis, taking the following parameters, 95% confidence and 5% error, and by calculating the sample size, a total of 200 animals to be analyzed in the post mortem inspection was estimated, The same was obtained from a population of 420 cattle that are slaughtered on average in the municipal slaughterhouse of the canton of Ventanas that exist between two months that the study lasted, on the other hand it was obtained as a result that of the 200 cattle inspected for Mycobacteriun bovis, through the post mortem analysis of organs, viscera and lymph nodes, 0 cases of antaomopathological alterations compatible with bovine tuberculosis were reflected, reporting 0% in positive cases and 100% in negative cases. In conclusion, during the study carried out on Mycobacterium bovis in slaughterhouses, there were no positive cases compatibles with the disease.